Multitemporal analysis of plant associations and land use changes in a high Andean locality, Puno-Peru - Loza-Del-Carpio, Alfredo (2021)
Unplanned changes in the use of high Andean territories have become more evident, leading to a loss of productive areas and important ecosystem services. Under this context, the objective of this study was to characterize the temporal changes in vegetation and land use in the high Andean district of Cabana (Peru). Vegetation types were determined based on the predominant species; these areas, together with the frequent forms of land use, were quantified using a supervised analysis of Landsat images with a 30 m spectral resolution, obtained during March and April 2000, 2005, 2010, and 2016. Six types of plant associations were identified whose areas decreased 2000 ha, from the initial 12500 in 16 years (16.27%). By 2000 the Muhlenbergetum fastigiatae association had the highest coverage (43.96%), but in 2016 Calamagrostio vicunaro - Festucetum dolichophyllae predominated (47.31%). Crop areas increased from 5133 ha (27%) to 7115 ha (37%) of the district surface, while degraded soils extended from 35 to 120 ha, sparsely vegetated areas from 17 to 30 ha and wetland reduced from 179 to 29.7 ha. Urban coverage grew 40.7 % annually. Land use with no territorial ordering basis caused detriment in vegetation and compromised the sustainable use of natural resources.